Mexican American Adolescent Mothers' Lived Experience: Grounded Ethnicity and Authentic Mothering. (May 2019) - Sommer, Phyllis A.; Kelley, Michele A.; Norr, Kathleen F.; Patil, Crystal L.; Vonderheid, Susan C.
We conducted this qualitative, phenomenological study to further understanding of how second-generation Mexican American adolescent mothers perceive their young motherhood experience, drawing on the context of their Mexican heritage background. Through in-person interviews with 18 young mothers, we discerned shared essential meanings reconstructed around two major domains: (a) grounded ethnicity, a firm desire to remain true to and share their heritage culture, and (b) authentic mothering, strong relationality to their infants. We found that young mothers embraced their Mexican heritage mothering approaches, such as fostering familismo, valuing family above other obligations. The adolescents in this study sensed their young motherhood as an opportunity to protect and improve qualities of traditional familial cultural heritage, while absorbing elements of American culture to enhance the future for themselves and their infants. We discuss how providers can help reduce stigmatization and promote self-efficacy by respecting and partnering with young mothers to provide culturally congruent services.